The Thatcher and Major Governments and the Union of Democratic Mineworkers, c. 1985–1992. Issue 40 (September 2019) - Daniels, Steven
Abstract : Often now forgotten, the Union of Democratic Mineworkers (UDM) is a breakaway organization formed after the 1984–85 miners' strike, based primarily in Nottinghamshire. Formed in opposition to the policy and conduct of the National Union of Mineworkers (NUM) during the strike, newly available archival material has revealed that it received considerable support from the Conservative government, which sought to discourage 'extremist' trade unions such as the NUM and to promote 'moderate' unions. This article explores that relationship, demonstrating how the UDM was encouraged and rewarded for fitting the Thatcherite model of a 'moderate' trade union, and analyses its subsequent decline once that support was removed. Using the framework of Claus Offe and Helmut Wiesenthal, and Walther Müller-Jentsch, it assesses the extent to which the UDM was a 'hybrid' organization, displaying features of both an independent and company union.